Avaliação numérico-experimental da distribuição de tensões geradas pela contração de polimerização de resinas compostas - Baggio, Rafael (2010)
The purpose of this study was to evaluate the distribution of the stresses generated by the polymerization shrinkage of three composite resins [FiltekTM Z250 (3M ESPE, St. Paul, Minn., USA); FiltekTM Z350 (3M ESPE, St. Paul, Minn., USA) and P-90 (3M ESPE, St. Paul, Minn., USA)], with mechanical tests and finite element analysis (FEM). Ten samples of each composite resin were prepared in metal matrix of 25 X 2 X 2 mm and were tested in the flexural 3 points bend strength in a universal testing machine and a cross-head speed of 0.5 mm / min. After, more 10 samples of each composite resin were prepared in a metal matrix in the form of an hourglass measuring 10 x 3 x 1.5 mm with a central bottleneck of 1.5 mm were submitted to a tensile strength in an universal testing machine with a load cell of 10 N and a crosshead speed of 1.0 mm / min until material failure occurred. After, FEM analysis was made simulating the effects of a class V restoration. In the mechanical tests of tensile strength (MPa) and 3 points bend flexural strength (MPa) respectively, all composites obtained similar results, being to FiltekTM Z-250 (36.51 ± 8.14 and 158.51 ± 31.80), to FiltekTM Z-350 (34.43 ± 6.49 and 146.65 ± 18.83) and to FiltekTM P90 (37.35 ± 7.51 and 148.00 ± 26.24) with no statistical differences by Two-way ANOVA test andBonferroni (alpha = 0.05) post-hoc. In the FEM analysis, the silorane based resin (FiltekTM P90) showed lower values of tension produced by polymerization shrinkage and better able to dissipate it by the adjacent structures.